A human monoclonal antibody against the distal carboxyl terminus of ADAMTS‐13 modulates its susceptibility to an inhibitor in thrombotic thrombocytopenic purpura. (11th May 2021) - Halkidis, Konstantine; Siegel, Don L.; Zheng, X. Long
Abstract: Background: Immune thrombotic thrombocytopenic purpura (iTTP) is a potentially fatal thrombotic microangiopathy, resulting from a severe deficiency of plasma ADAMTS‐13 (A Disintegrin And Metalloproteinase with ThromboSpondin type 1 motif, member 13) activity. IgG‐type autoantibodies are primarily responsible for the inhibition of plasma ADAMTS‐13 activity. However, the mechanism underlying autoantibody‐mediated inhibition is not fully understood. Objective: The purpose of the present study is to determine the role of IgG autoantibodies against various carboxyl‐terminal domains of ADAMTS‐13 in regulating ADAMTS‐13 activity and its inhibition. Method: Various human monoclonal antibodies isolated by phage display, recombinant protein expression and purification, and biochemical analyses were employed for the study. Results: Our results demonstrate for the first time that a human monoclonal antibody fragment, the single chain fragment of the variable region (scFv) isolated from a patient with acute iTTP that binds the distal carboxyl‐terminus of ADAMTS‐13, is able to activate ADAMTS‐13 and increase the proteolytic cleavage of a FRETS‐VWF73 substrate; moreover, binding of such a human monoclonal antibody against the carboxyl‐terminus of ADAMTS‐13 to plasma ADAMTS‐13 appears to modulate inhibition by another human monoclonal antibody (i.e., scFv4‐20), also isolated from an iTTP patient, that targets the spacer domain of ADAMTS‐13. These results provide new insights into our understanding of the pathogenesis of iTTP.